The lipid-droplet-associated protein ABHD5 protects the heart through proteolysis of HDAC4 - Jebessa, Zegeye Hailu; Dewenter, Matthias; Lehmann, Lorenz; Xu, Chang; Schreiter, Friederike; Siede, Dominik; Jones, Barbara Christine; Federico, Giuseppina; Sauer, Sven; Fischer, Tamás; Müller, Oliver J.; Dieterich, Christoph; et al. (Nature metabolism, 2019)
Known as a regulator of lipolysis, ABHD5 is found to also act as a serine protease that cleaves HDAC4 in response to catecholaminergic stimulation, thus resulting in the formation of a polypeptide that protects against metabolic-stress-induced heart failure.
Das PDF enthält zusätzlich einen Anhang von 12 Seiten
Gesehen am 06.12.2019